Production of Traditional Grape Pickle Using Lactobacillus acidophilus and Investigation of the Inhibitory Effect of the Product on Bacillus cereus and Escherichia coli - Gülten Tiryaki Gündüz; Burcu Sıla Göral (Turkish Journal of Agriculture: Food Science and Technology, 2022)
Grape pickle is a traditional food that is made with grapes (Vitis vinifera), horseradish (Armoracia rusticana) and grape syrup. In this study, the survival of Bacillus cereus and Escherichia coli in grape pickles produced with or without using probiotic Lactobacillus acidophilus La-5 as well as microbiological, chemical and sensory properties of each group were examined during 35 days of ripening at 25°C and 5 months at refrigerated storage period. Molds and lactic acid bacteria (LAB) counts remained below the limit of detection (6 log in samples to be considered a probiotic product. E. coli counts rapidly declined to undetectable level within 7 days, while B. cereus numbers was found 1.56-1.72 log cfu/g at the end of the storage period. As a result, it was established that traditional grape pickle is not suitable food matrix for probiotication. High total soluble solid content (63 °Brix) and presence of horseradish in grape pickles ensure the microbiological stability as well as the safety of product.